تکریم ِانسانی اور مثلہ کی ممانعت:شرعی و قانونی جائزہ: Respect OF Humainity and Probition of body Multilation (Islamic and Legal Review) - Adil, Dr. Muhammad; Rahmani, Dr. Ziaullah (Al-Irfan, 2023)
Allah Ta’ala has made the "Man"- the highest creations among all creations and has given him such sanctity and dignity which is not limited to life but continues after death. That’s why in Islamic Shari’ah, clear orders have been given regarding the respect of the human body and it has not only been forbidden to do any kind of harm to it, but it has also made it obligatory to bury it with dignity and respect. Even the desecration of the dead body of a criminal who has committed the worst crimes and who has fought on behalf of the enemy in war is prohibited. But regrettably, in the recent past, both in peace and in war, there have been continuous incidents of desecration of human corpses, so the need was felt that in the life of a person, while giving death penalty for a crime or killing and after death, a Shari’a and legal approach based on honoring and respecting the human body should be brought forward. Keeping this need in mind, these three aspects have been examined in this Article under review, especially by mentioning the Quranic verses, Ahadith and the syings of Fuqaha, the Shariah ruling has been explained. Along with this, the current legal status of "Musla" has also been discussed in terms of international humanitarian law and other international laws.